Collective Woundedness: Exploring intergenerational trauma and healing in Barbara Boswell’s Grace, Mohale Mashigo’s The Yearning and Kopano Matlwa’s Period Pain - Cele, Andile Judith (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.